Autonomy among professional nurses – validation of the Dempster Practice Behavior Scale (DPBS) in Poland - Sadowska, Anna; Czarkowska-Pączek, Bożena (Nursing in the 21st Century, 2025)
Aim. A proper understanding of autonomy can enhance patient care, reduce occupational burnout, foster professional socialisation, and elevate the quality of work among nurses. The Dempster Practice Behavior Scale has been translated into several languages and is widely used in worldwide scientific research with favorable outcomes.Material and methods. The evaluation  of the credibility, reliability, and psychometric properties of the Polish version of the Dempster Practice Behavior Scale.Results. The  study involved the participation of 338 nurses and utilised the DPBS questionnaire. To validate the DPBS questionnaire, a Confirmatory Factor Analysis (CFA) was performed, an Exploratory Factor Analysis (EFA) with Varimax rotation was undertaken alongside Horne’s parallel analysis and scree plot adoption. The reliability of the questionnaire was assessed through Pearson’s r correlation and Cronbach’s alpha coeﬃcient, considering values greater than 0.7 as satisfactory.Conclusions. The parallel analysis yielded four primary factors and corresponding item subgroups, accounting for 47.6% of the total variance. Factor loadings varied between 0.40 and 0.72. The Polish version of DPBS-P exhibits a high-reliability score, making it a standardised tool for measuring nurse autonomy. Cultural adaptation necessitated altering the number of items and corresponding names of the DPBS-P factors.